A study of the deflections of metal road guardrail elements - Prentkovskis, Olegas; Beljatynskij, Andrey; Prentkovskienė, Rasa; Dyakov, Ivan; Dabulevičienė, Laima (Transport, 2009)
Statistical data on traffic accidents in 2008 in Lithuania is presented. Referring to statistical data, grounding on an obstacle’ makes one‐tenth of all registered traffic accidents ‐ 9.4% (an obstacle may be a road guardrail, a lamp post, a tree, a bar, a gate, etc.). Road guardrails of various types are installed on the shoulders and dividing strips of urban and suburban roads. They are as follows: reinforced concrete guardrails, cable guardrails and metal guardrails. Metal guardrails, consisting of S‐shape metal posts and a protective W‐shape horizontal beam, are most popular. The authors of the present paper examine the deformation processes of the elements of the above mentioned guardrail. A mathematical model of metal road guardrail was developed. Metal road guardrail was modelled using one‐dimensional first‐order finite elements, taking into account only elastic deformations, as well as the effect of soil on the buried post section of the guardrail. Based on the developed mathematical model of metal road guardrail, the deflections of its elements caused by the impact of a vehicle moving at varying speed were determined. The obtained values of deflections of guardrail elements (a protective W‐shape horizontal beam and a S‐shape post) presented in paper do not exceed the admissible values (of beam deflections).First published online: 27 Oct 2010